Two-pronged Rhetorics in Contemporary America - Stuchel, Viktor (Univerzita Pardubice, 2020)
This thesis deals with the contrastive rhetorics of Donald J. Trump and Hillary R. Clinton during their journey as presidential candidates for the Oval Office during the 2016 American elections. The first part delves into the history of current American political system by portraying Alexander Hamilton and his centralised fiscal and federal government policies against his rival, Thomas Jefferson, who preferred a collection of strong and independent agrarian states. The second part creates theoretical foundation on different conceptual metaphors explored by G.Lakoff, M.Johnson and other linguists. The corpus analysis, which is preceded by chapter dedicated to some background information on the presidential candidates, uses the already established theory in order to find conceptual metaphors which should help to further interpret the intended meaning in their respective speeches.
Dvojí rétorika dnešní Ameriky
Keywords: Clinton, Hillary; Trump, Donald; rétorika; konceptuální metafora; prezidentské volby; obrazný jazyk; Clinton, Hillary; Trump, Donald; rhetorics; conceptual metaphor; presidential elections; figurative language